Synonymical and nomenclatural notes on Trachyderini (Coleoptera, Cerambycidae, Cerambycinae) - Monné, Marcela L.; Monné, Miguel A. (Zootaxa, 2013)
Megaderus is reinstated and attributed to Germar, 1824 and not to Rafinesque, 1815 or Dejean, 1821; Neomegaderus Monné, 2006 is an unnecessary replacement name; Purpuricenus brasiliensis Schaufuss, 1871 is a synonym of Eriphus purpuratus Chevrolat, 1862; Panchylissus Waterhouse, 1880 is a synonym of Galissus Dupont, 1840 and G. rubiventris Martins & Galileo, 2010 a synonym of G. cyaneipennis (Waterhouse, 1880), comb. nov.; Panchylissus nigriventris Lane, 1965 is transferred to Galissus; a key to the species of Galissus is provided; the female of Poecilopeplus fontanieri (Lucas, 1857) is described; Ischnotes Newman, 1840 currently in Trachyderini, Ancylocerini is transferred to incertae sedis of Cerambycinae.